The Role of Forensic Accounting in Detecting Economic Crimes - Polycarp, Saman Udi (2019)
The role forensic accounting plays in detracting crime and corruption in both public sector and private sector is the major focus of these journal. The objective of the research work seeks to discover the role a forensic accountant can play in the contest against crime by applying its investigative skills, providing litigation support service and documentation and reporting. The research design employed was the survey research. Data were majorly collected from primary sources. A well-structured 5 point likert scale questionnaire was used to elucidate information from the respondents, these results were analyzed using tables, simple percentages, and statistical analysis techniques chi-square and the results was used to validate or invalidate the hypotheses. The results of the empirical findings show that forensic accountants are relevant in investigating crime and corruption in both private and public sector in Nigeria. Forensic accountants play a role in litigation support services in organizational sector(s), and forensic accountants are relevant in documentation and reporting. It was detected that the forensic accountants play a significant role in shortening crime and corrupt practices in any sector since they provide a mechanism to hold people answerable, such that those who manage resources in a fiduciary capacity do not easily abuse that trust without detection. Amongst other proffered solutions, it was recommended that accounting professionals should always be proactive such that the members of the profession in Nigeria are kept abreast of emerging technologies, especially in the area of forensic accounting. Keywords:Forensic Accounting, forensic accountants,economic and financial crime DOI: 10.7176/RJFA/10-16-11 Publication date: August 31st 201